Nanostructural Features of Silver Nanoparticles Powder Synthesized through Concurrent Formation of the Nanosized Particles of Both Starch and Silver - A. Hebeish; M. H. El-Rafie; M. A. El-Sheikh; Mehrez E. El-Naggar (Journal of Nanotechnology)
Green innovative strategy was developed to accomplish silver nanoparticles formation of starch-silver nanoparticles (St-AgNPs) in the powder form. Thus, St-AgNPs were synthesized through concurrent formation of the nanosized particles of both starch and silver. The alkali dissolved starch acts as reducing agent for silver ions and as stabilizing agent for the formed AgNPs. The chemical reduction process occurred in water bath under high-speed homogenizer. After completion of the reaction, the colloidal solution of AgNPs coated with alkali dissolved starch was cooled and precipitated using ethanol. The powder precipitate was collected by centrifugation, then washed, and dried; St-AgNPs powder was characterized using state-of-the-art facilities including UV-vis spectroscopy, Transmission Electron Microscopy (TEM), particle size analyzer (PS), Polydispersity index (PdI), Zeta potential (ZP), XRD, FT-IR, EDX, and TGA. TEM and XRD indicate that the average size of pure AgNPs does not exceed 20 nm with spherical shape and high concentration of AgNPs (30000 ppm). The results obtained from TGA indicates that the higher thermal stability of starch coated AgNPS than that of starch nanoparticles alone. In addition to the data obtained from EDX which reveals the presence of AgNPs and the data obtained from particle size analyzer and zeta potential determination indicate that the good uniformity and the highly stability of St-AgNPs).